Brexpiprazole inhibits EMT and migration of colorectal cancer cells by downregulating the SREBP1/SNAI1 signaling pathway - Liu, Xiaojie; He, Jingyi; Ma, Ao; Xia, Wenjun; Xia, Zhiyang; Liu, Lu; Wu, Zhuoze; Chen, Wei (Frontiers in Oncology, 2026)
ObjectiveTo investigate the role and mechanism of the SREBP1/SNAI1 signalling pathway in the effect of brexpiprazole on the EMT and metastasis of CRC.MethodsThe effects of different concentrations of brexpiprazole on cell migration, cell invasion and protein expression in vitro were examined by cell scratch assays, Transwell assays, Western blotting, ELISA, immunofluorescence, and transmission electron microscopy. A dual-luciferase reporter gene assay was used to assess the interactions between SREBP1 and SNAI1. A model of CRC metastasis in nude mice was established, and Western blotting, HE staining, and PET/CT were utilised to explore the effects of brexpiprazole on CRC lung metastasis.ResultsBrexpiprazole significantly inhibited the migration and invasion of CRC cells; downregulated the expression of SREBP1(m), SNAI1 and MMP9; upregulated the expression of E-Cad and ZO1; and decreased the levels of secreted ICAM-1 and VEGF in the supernatant of CRC cells. Western blotting and dual-luciferase assays revealed that SREBP1 could directly regulate the expression of SANI1. On the other hand, in vivo experiments revealed that brexpiprazole significantly inhibited the formation of CRC lung metastases, suppressed the expression of SREBP1(m), SNAI1and MMP9, and upregulated the expression of E-Cad and ZO1.ConclusionBrexpiprazole inhibits the migration, invasion and metastasis of CRC cells by inhibiting the SREBP1/SNAI1 signalling pathway and downregulating the expression of EMT-related factors.